Phages in Therapy and Prophylaxis of American Foulbrood – Recent Implications From Practical Applications - Jończyk-Matysiak, Ewa; Popiela, Ewa; Owczarek, Barbara; Hodyra-Stefaniak, Katarzyna; Świtała-Jeleń, Kinga; Łodej, Norbert; Kula, Dominika; Neuberg, Joanna; Migdał, Paweł; Bagińska, Natalia; Orwat, Filip; Weber-Dąbrowska, Beata; et al. (Frontiers in Microbiology, 2020)
American foulbrood is one of the most serious and yet unsolved problems of beekeeping around the world, because it causes a disease leading to the weakening of the vitality of honey bee populations and huge economic losses both in agriculture and horticulture. The etiological agent of this dangerous disease is an extremely pathogenic spore-forming bacterium, Paenibacillus larvae, which makes treatment very difficult. What is more, the use of antibiotics in the European Union is forbidden due to restrictions related to the prevention of the presence of antibiotic residues in honey, as well as the global problem of spreading antibiotic resistance in case of bacterial strains. The only available solution is burning of entire bee colonies, which results in large economic losses. Therefore, bacteriophages and their lytic enzymes can be a real effective alternative in the treatment and prevention of this Apis mellifera disease. In this review, we summarize phage characteristics that make them a potentially useful tool in the fight against American foulbrood. In addition, we gathered data regarding phage application that have been described so far, and attempted to show practical implications and possible limitations of their usage.